2015
DOI: 10.1186/s12991-015-0079-6
|View full text |Cite
|
Sign up to set email alerts
|

Disability assessment as an outcome measure: a comparative study of Nigerian outpatients with schizophrenia and healthy control

Abstract: Background and objectiveSchizophrenia is a chronic mental disorder that leads to disability in several aspects of the individual’s personal, social, and occupational functioning. This study assesses and compares the level of disability among Nigerian outpatients with schizophrenia and healthy controls (HC).MethodsA comparative cross-sectional study among 100 schizophrenia outpatients with an ICD-10 diagnosis and 100 HC was conducted over a 4-month period. They completed a questionnaire containing the Zung’s Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 36 publications
4
27
1
Order By: Relevance
“…While the WHODAS has heretofore been used primarily to assess disability associated with physical illnesses, the WHODAS is being increasingly applied to study disability among psychiatric populations in low- and middle-income countries. For example, it has been applied to assess functional impairments associated with mental disorders, understand relationships between mental illness and physical comorbidities, and measure mental health treatment outcomes (Akinsulore et al 2015 , De Silva et al 2015 , Faye et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the WHODAS has heretofore been used primarily to assess disability associated with physical illnesses, the WHODAS is being increasingly applied to study disability among psychiatric populations in low- and middle-income countries. For example, it has been applied to assess functional impairments associated with mental disorders, understand relationships between mental illness and physical comorbidities, and measure mental health treatment outcomes (Akinsulore et al 2015 , De Silva et al 2015 , Faye et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…found out that the patients with chronic schizophrenia reported greater disability in an individual's personal, social, and occupational life. [23] In this study, disability burden in patients with chronic schizophrenia having duration of more than 20 years is much more than schizophrenia patients having duration of 5 years.…”
Section: Discussionmentioning
confidence: 81%
“…Studies looking at the association between clinical variables and QoL have reported a significant association between the number of daily medication, the presence of anxiety/depression symptoms, suicidality, comorbid medical problems and general psychopathology79,34,35,36 and medication adherence 9,37. According to Akinsulore et al, the presence of depressive symptoms, negative and positive symptoms of schizophrenia and frequency of relapse also predicts greater disability in patients with schizophrenia 36…”
Section: Discussionmentioning
confidence: 99%